2009
DOI: 10.1007/s00428-009-0855-2
|View full text |Cite
|
Sign up to set email alerts
|

DcR1 expression in endometrial carcinomas

Abstract: The tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) is a member of the TNF family, which mediates apoptosis by the extrinsic pathway. Up-regulation of decoy receptors, DcR1 and DcR2, may result in diminished binding of TRAIL to their functional receptors. DcR1 expression was assessed in normal endometrial tissue (NE) and endometrial carcinoma (EC) samples by immunohistochemistry (IHC) and quantitative real-time polymerase chain reaction (PCR). IHC was performed in two tissue microarrays; one co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 24 publications
(42 reference statements)
0
7
0
1
Order By: Relevance
“…Similarly, the cytoplasmic expression of DcR1 and DcR2 was reported, e.g., in primary and metastatic brain tumors [8] and in prostate cancer [27]. In endometrial cancer, DcR1 cytoplasmic expression was evaluated by Tarragona et al [15]. The authors studied 62 cases of endometrial cancers by tissue microarray, and found DcR1 to be present in 98.1 % of cases [15].…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…Similarly, the cytoplasmic expression of DcR1 and DcR2 was reported, e.g., in primary and metastatic brain tumors [8] and in prostate cancer [27]. In endometrial cancer, DcR1 cytoplasmic expression was evaluated by Tarragona et al [15]. The authors studied 62 cases of endometrial cancers by tissue microarray, and found DcR1 to be present in 98.1 % of cases [15].…”
Section: Discussionmentioning
confidence: 96%
“…In contrast to this, Koornstra et al [9] describe a lack of correlation of DR4 and DR5 cytoplasmic expression with grading and staging in cancer of the colon, and Zhuang et al [28] found DcR1 and DcR2 cytoplasmic expression not to be related to progression of neoplasmic disease. In endometrial cancer patients, Tarragona et al [15] did not confirm the association of DcR1 expression with histological type of the cancer (EAC vs. non-EAC), its grade and stage, as well.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In EAC, this may be at least in part due to the over expression of the decoy receptor DcR1. It has been demonstrated that DcR1 is over expressed in EAC and it competitively inhibits the attachment of the TRAIL ligand to the DD receptors [55]. An interesting study by Dolcet et al demonstrated that TRAIL fails to trigger apoptosis in endometrial cancer cells, indicating resistance probably mediated by the FLICE-inhibitory protein (FLIP) [56].…”
Section: Trailmentioning
confidence: 97%